The Complementary Role of ToF-SIMS in the Assessment of Imiquimod Permeated into the Skin from a Microemulsion Dosage Form - Mohammed Hussain Al-Mayahy; Maria Marlow; David J. Scurr (College of Pharmacy / Mustansiriyah University, 2019)
The assessment of drug permeation into/across the skin is traditionally accomplished using Franz diffusion cells with subsequent analysis by conventional chromatographic methods such as HPLC and more recently using advanced imaging techniques. In this context, time   of flight-secondary ion mass spectrometry (ToF-SIMS) offers distinctive advantages in mapping drugs within skin with high sensitivity and chemical specificity without the need for fluorescent tags or radiolabels. The work in this paper uses the combination of conventional and advanced methods to evaluate imiquimod permeation into the skin. This approach provides complementary and detailed information regarding the permeated mass, the permeation depth and the spatial distribution and localisation of drugs within skin. Imiquimod is an immune modulator drug approved by the FDA for the treatment of superficial basal cell carcinoma (BCC) but not the nodular lesions. As other studies have reported that Aldara™ cream (imiquimod 5% w/w) has some limitations in the treatment of nodular BCC lesions due to the cream's inability to deliver imiquimod into the deeper more invasive nodular lesions, an enhancement of imiquimod permeation is thought to be useful to overcome these limitations. Therefore, an attempt to improve delivery of imiquimod into the deeper skin layers using microemulsions was investigated. Imiquimod microemulsions were formulated and characterised in our previous work are now tested for skin permeation enhancement. However, the assessment of imiquimod permeation from the formulated microemulsions using HPLC and ToF-SIMS demonstrated a limited ability of the microemulsions to improve delivery of imiquimod over Aldara™ cream. This was attributed to the poor release of imiquimod from the microemulsion formulas due to the high affinity of imiquimod for the oil phase and the encapsulation of the oil droplets by the S/Co-S mixture. This is thought to be, the first time that ToF-SIMS has been used to assess permeation of imiquimod from a microemulsion dosage form.